Basic Legal Study On Workplace Health And Safety Protection In Indonesia - Malau, Parningotan (Technium Social Sciences Journal, 2020)
This study aims to examine the legal history and the concretization of the value of Pancasila as a legal basis in protecting the occupational safety and health of workers in Indonesia. The research method used in this study is a type of normative research using the Statute Approach. The analysis technique in this study was carried out in a descriptive way to describe the legal conditions and protection of workers in Indonesia. The results of this study indicate that the birth of labor law in Indonesia is based on a long history of labor suffering due to slavery, forced cultivation, slavery to forced labor, not vice versa because employers corporations are persecuted by the treatment of workers and employers. National labor law, specifically the Work Safety Health Act, must be able to position workers as independent legal subjects, not arbitrarily controlled by other legal subjects, be treated humanely in accordance with their dignity and status, and obtain justice as a weak party. In addition, to avoid discrimination, it must show the principle of unity in work relations, between employers and workers in corporations, or broader unity in industrial relations, namely between employers’ organizations, labor organizations, and government